Roadmap for the scaling up of Agroecology in Ecuador - Valdivia Diaz, Merelyn; Le Coq, Jean-François (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
An analysis of existing policies, programs and limiting factors.